Characteristics of the microbiocenosis of the vaginal tract and its role in initiating inflammatory process in endometrium in women with reproductive disorders - I. N. Danusevich; E. I. Ivanova; I. M. Mikhalevich (Acta Biomedica Scientifica, 2017)
Background. Microbiological disorders in the genital tract predispose to the development of chronic pelvic diseases and subsequently worsen the prognosis for reproductive function, causing infertility, miscarriage. Aims: study of the microbiocenosis of the vaginal tract and its role in initiating inflammatory process in endometrium in women with reproductive disorders. Materials and methods. The study included 50 patients with reproductive disorders with histological confirmation of the diagnosis of chronic endometritis and 50 patients with reproductive disorders without chronic endometritis. Microbiological studies of the biotope of the vagina were carried out according to the guidelines. The counting of immune cells was carried out in peripheral blood with flow cytofluorimeter. Methods of mathematical statistics implemented in the application package Statistica 6.1 (StatSoft Inc., USA) were used in the study. Used criteria were Student's t-test and Fisher criterion with a significance level less than 5 % (p < 0.05). Results and conclusions. Conditionally pathogenic microflora in women with chronic endometritis in the cervical canal is represented by candidiasis, herpesviruses, ureaplasma and facultative-anaerobically positive microorganisms. Candida, obligate-anaerobic gram-negative, and facultative anaerobic gram-positive microorganisms predominated in the endometrium. The secondary immunodeficiency state is characterized by suppressor activity of T-lymphocytes; the decrease in microbicide activity of blood, pronounced inhibition of the humoral link of the immune system. Violations of the balance of the indigenous and conditionally pathogenic microflora accompanied by a secondary immunodeficiency may be the initiator of chronic inflammation in the endometrium.